From Bladder to Joints: Reactive Arthritis Secondary to Intravesical-Bacillus Calmette-Guérin Immunotherapy - Edavalath, Sukesh; Palakkal, Shahsadhi Ittikapparambil; Achamveetil, Shinad (Indian Journal of Pharmacy Practice)
Reactive arthritis is a rare complication following Bacillus Calmette-Guérin (BCG) therapy for bladder cancer, often presenting with joint pain and systemic symptoms. A patient with high-risk non-muscle-invasive bladder cancer underwent Transurethral Resection of the Bladder Tumor (TURBT) followed by 4 doses of intravesical BCG therapy. Four weeks after treatment, the patient developed bilateral knee pain, swelling, difficulty walking, and fever, consistent with BCG-induced reactive arthritis. The patient’s symptoms improved with oral prednisolone, and BCG therapy was discontinued. A flare during steroid tapering was managed with methylprednisolone and sulfasalazine. At follow-up, C-Reactive Protein (CRP) levels normalized, indicating clinical improvement. BCG-induced reactive arthritis, though rare, should be considered in patients presenting with new-onset arthritis after BCG therapy. Early recognition and appropriate treatment are crucial for optimal management.
Keywords: Intravesical BCG Therapy; Reactive Arthritis; TURBT; Bladder Tumor